NIRS and iSPA-PLS for predicting total anthocyanin content in jaboticaba fruit - Torres Mariani, Nathalia Cristina; Almeida Teixeira, Gustavo Henrique de [UNESP]; Gomes de Lima, Kassio Michell; Morgenstern, Thayara Bittencourt; Nardini, Viviani; Cunha Júnior, Luis Carlos (Elsevier B.V., 2015)
The aim of this study was to evaluate the potential of the successive projection algorithm for interval selection in partial least squares (iSPA-PLS) together with near-infrared reflectance spectroscopy (NIRS) as a feasible method to determine the total anthocyanin content (TAC) of intact jaboticaba fruit [Myrciaria jaboticaba (Vell.) O. Berg]. A total of 579 jaboticaba fruit were collected in three different harvests in three separate years (2011 and 2013). The correlation coefficients between the predicted and measured TAC were between 0.65 and 0.89, the RMSEPs were 7.55 g kg(-1) and 9.35 g kg(-1) (good accuracy) for prediction set, respectively. The RPD ratios for TAC were in the range of 2.57-3.19 with iSPA-PLS, which showed better predictive performance (acceptable precision). These results suggest that the NIR spectroscopy and wavelength selection (iSPA-PLS) algorithm can be used to determine the TAC of intact jaboticaba fruit. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: NIRS; iSPA-PLS; Wavelength selection; Jaboticaba; PLS